Labor Education Course for College Students in the New Era - Deep Integration of Theory and Practice - Luo , Xiaoyong (Journal of Theory and Practice of Contemporary Education, 2023)
Labor is a special form of human movement and the foundation for human survival and development; College students, as the main talents cultivated by the country, have cutting-edge thinking and are one of the main forces driving social development. Therefore, it is particularly important for college students to establish a correct view of labor, cultivate their enthusiasm for labor, and guide them to respect and love labor; However, the current situation is that many higher education institutions only focus on the theoretical level of labor education for college students, and have not yet deeply integrated it with practice, resulting in a disconnect between theory and practice; This article takes the Law Department of Foft Science and Technology College in Foft City as an example to explore and study the integration of theory and practice in labor education courses. Based on such a living environment, ""Er"" shows many customs and habits of the Ewenki people that have been integrated into their normal life: they hunt for fork fish, herd reindeer, dry dried meat, brew milk tea, bake Greeba cakes, and gather around barbecue, drink and dance over a bonfire. Here, the Ewenki people, who have lived in the jungle for generations, cling to nature and become the real citizens of mountains and forests. In accordance with the laws of nature, they make food or clothing from animals and plants to ensure the smooth continuation of tribal life. Here, the existence of life and the natural environment have reached a state of harmony and unity. But at the same time, life also has a more direct and profound experience of the primitive and barbaric nature. Naturally appeared in front of the Ewenki people with a more real face, and although they gave birth to them, they also threatened them. There are always many irresistible natural disasters in the borderlands. ""Er"" describes an extremely tragic snowstorm disaster: when the wind and snow comes, the fragility of life in nature is fully revealed, and the only thing they can do is strive to protect yourself, any rebellion against Feng Xue will be severely and completely destroyed. In this merciless snowstorm, the reindeer on which the Ewenki people depended also suffered heavy losses, casting a heavy shadow over their lives. This is the experience of people living in the borderlands of a more immediate and cruel existence.